A systematic review and network meta‐analysis comparing the use of Foley catheters, misoprostol, and dinoprostone for cervical ripening in the induction of labour. (5th November 2015) - Chen, W; Xue, J; Peprah, MK; Wen, SW; Walker, M; Gao, Y; Tang, Y
Abstract : Background: Various methods are used for cervical ripening during the induction of labour. It is still debatable which of these methods of treatment is optimal. Objective: To compare treatment techniques for cervical ripening in the induction of labour. Search strategy: Medline, Embase, and the Cochrane Collaboration databases were searched using the keywords 'cervical ripening', 'labour induced', 'misoprostol', 'dinoprostone', and 'Foley catheter'. Selection criteria: Randomised controlled trials (RCTs) of cervical ripening during the induction of labour, evaluating rates of failure to achieve vaginal delivery within 24 hours, incidence of uterine hyperstimulation with fetal heart rate (FHR) changes, and rates of caesarean section. Studies including women with prelabour rupture of membranes were excluded. Data collection and analysis: Outcome data were collected and analysed through pairwise meta‐analysis and network meta‐analysis within a Bayesian framework. Main results: A total of 96 RCTs (17 387 women) were included in the meta‐analysis. Vaginal misoprostol was the most effective cervical ripening method to achieve vaginal delivery within 24 hours, but had the highest incidence of uterine hyperstimulation with FHR changes. The use of a Foley catheter to induce labour was associated with the lowest rate of uterine hyperstimulation accompanied by FHR changes. The caesarean section rate was lowest using oral misoprostol for the induction of labour. Author's conclusions: No method of labour induction demonstrated overall superiority when considering all three clinical outcomes. Decisions regarding the choice of induction method will depend upon the relative preference for effecting vaginal delivery within 24 hours, minimising the incidence of uterine hyperstimulation with adverse FHR changes and avoiding caesarean section. Tweetable abstract: Oral misoprostol for the induction of labour is safer than vaginal misoprostol and has the lowest rate of caesarean section. Tweetable abstract: Oral misoprostol for the induction of labour is safer than vaginal misoprostol and has the lowest rate of caesarean section.